Electrodeposited Ternary Metal (Oxy)Hydroxide Achieves Highly Efficient Alkaline Water Electrolysis Over 1000 h Under Industrial Conditions - Chunfa Liu; Haoyun Bai; Jinxian Feng; Keyu An; Lun Li; Zhichao Yu; Lulu Qiao; Di Liu; Shuyang Peng; Hongchao Liu; Hui Pan (Carbon Energy)
ABSTRACT Large‐scale green hydrogen production technology, based on the electrolysis of water powered by renewable energy, relies heavily on non‐precious metal oxygen evolution reactions (OER) electrocatalysts with high activity and stability under industrial conditions (6 M KOH, 60°C–80°C) at large current density. Here, we construct Fe and Co co‐incorporated nickel (oxy)hydroxide (Fe2.5Co2.5Ni10OyHz@NFF) via a multi‐metal electrodeposition, which exhibits outstanding OER performance (overpotential: 185 mV @ 10 mA cm−2). Importantly, an overwhelming stability for more than 1100 h at 500 mA cm−2 under industrial conditions is achieved. Our combined experimental and computational investigation reveals the surface‐reconstructed γ‐NiOOH with a high valence state is the active layer, where the optimal (Fe, Co) co‐incorporation tunes its electronic structure, changes the potential determining step, and reduces the energy barrier, leading to ultrahigh activity and stability. Our findings demonstrate a facile way to achieve an electrocatalyst with high performance for the industrial production of green hydrogen.